Bulletin on food price dynamics, inflation, and the food security situation in Sudan: January 2023 - Ahmed, Mosab O. M.; Siddig, Khalid (International Food Policy Research Institute, 2023)
International prices of food commodities continued to decrease in January 2023 especially for vegetable oils, sugar, dairy, and meat. Resulting in further sluggish overall price inflation in January 2023 of 83.6 compared to 87.3 percent in December 2022. The national retail prices of food commodities in January 2023 increased slightly compared to December 2022. Fluctuations in the exchange rate were associated with the change in local prices of imported commodities such as wheat and sugar. Food prices in relatively unstable states were higher than the national average. The monthly inflation rate of food and beverages decreased by 0.2 percent in January 2023 compared to December 2022 driven by the declining CPI for the vegetables and fruits.